Ethnic development of the people of Russia and prospects of formation of the Russian nation - Erokhina, Elena A. (The New Research of Tuva, 2010)
The article presents an overview of the work of the The All-Russia scientific conference of the Russian society of sociologists «Ethnos. The nation. A society: the Russian reality and prospects» (1-3 November of 2010) in Moscow.